Hubungan Usia Kehamilan Dengan Komplikasi Pada Bayi Baru Lahir Di Rs Aura Syifa Kabupaten Kediri Tahun 2017 - Maharani Sulistiyo Putri; Ira Titisari; Arika Indah Setyarini (coba, 2017)
The age of mother pregnancy is a time limit of mothers pregnant, which is calculated from the first day of the last menstrual period. Normal gestational age is 40 weeks or 280 days as is the custom of 9 months 10 days as in postterm pregnancy. Postterm pregnancy is a pregnancy lasting > 42 weeks. Postterm gestational age tends to have a greater risk of giving birth to infants with complications such as asphyxia, macrosomia and perinatal mortality. This may be because placental function achieves peak at 38 weeks' gestation and then decreases after 42 weeks of gestation. As a result of aging placenta, the supply of food and oxygen to the fetus decreases and the uteroplacental circulation is only about 50%. The purpose of this study was to determine the relationship between gestational age with complications in newborns. The research design use analytic survey with cross sectional approach, population is taken as many as 210 respondents with sampling technique that is using purposive sampling then the big sample taken using finite formula and found the sample of 137 respondents who meet inclusion criteria. The instrument used is the medical record of patients in January - Juni 2016, measuring instrument used is documentation sheet, then data analysis in this study using crosstab conclusion from result no relation between gestational age with complication in newborn. Keywords: Pregnancy Age, Postterm Pregnancy, Asphyxia, Macrosomia, Perinatal Death.